7.1.31-eg-1 - From f(5 =-2 it follows that f-1-2 = 5 and...

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
Example Let f ( x ) = ( x - 3) 2 - 6 ,x 3. Find the value of df - 1 dx at the point x = - 2 = f (5). By the Inverse Function Theorem, df - 1 dx ± ± ± ± ± x = - 2 = ( f - 1 ) 0 ( - 2) = 1 f 0 ( f - 1 ( - 2)) , (provided f 0 ( f - 1 ( - 2)) 6 = 0.)
Background image of page 1
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: From f (5) =-2 it follows that f-1 (-2) = 5, and with f ( x ) = 2 x-6, ( f-1 ) (-2) = 1 f (5) = 1 4 ....
View Full Document

This note was uploaded on 04/02/2012 for the course MTH 132 taught by Professor Kihyunhyun during the Fall '10 term at Michigan State University.

Ask a homework question - tutors are online